2018
DOI: 10.3389/fphys.2018.00397
|View full text |Cite
|
Sign up to set email alerts
|

Development of a High-Throughput Flow Cytometry Assay to Monitor Defective Trafficking and Rescue of Long QT2 Mutant hERG Channels

Abstract: Long QT Syndrome (LQTS) is an acquired or inherited disorder characterized by prolonged QT interval, exertion-triggered arrhythmias, and sudden cardiac death. One of the most prevalent hereditary LQTS subtypes, LQT2, results from loss-of-function mutations in the hERG channel, which conducts IKr, the rapid component of the delayed rectifier K+ current, critical for cardiac repolarization. The majority of LQT2 mutations result in Class 2 deficits characterized by impaired maturation and trafficking of hERG chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 51 publications
1
41
0
Order By: Relevance
“…Quantification of mean QD 655 fluorescence indicated that BBS-hERG 1a-YFP alone or when combined with hERG 1b-CFP displayed similar surface density (Figure 5C, 2% increase or from surface density 1.0, n = 12 separate cultures, to 1.02 ± 0.05, 8 separate cultures), in line with published data, indicating hERG 1a traffics independently of hERG 1b to the cell surface in heterologous cells (Phartiyal et al, 2008). Negative controls expressing untagged hERG 1a and 1b displayed no QD 655 fluorescence (averaged surface density was 0.18 ± 0.006, five separate cultures), confirming that the red fluorescence signal was specific and only detected the BBS tag, consistent with our previous reports on KCNQ1 trafficking in HEK293 cells and cardiomyocytes (Aromolaran et al, 2014; Kanner et al, 2018).…”
Section: Resultssupporting
confidence: 90%
“…Quantification of mean QD 655 fluorescence indicated that BBS-hERG 1a-YFP alone or when combined with hERG 1b-CFP displayed similar surface density (Figure 5C, 2% increase or from surface density 1.0, n = 12 separate cultures, to 1.02 ± 0.05, 8 separate cultures), in line with published data, indicating hERG 1a traffics independently of hERG 1b to the cell surface in heterologous cells (Phartiyal et al, 2008). Negative controls expressing untagged hERG 1a and 1b displayed no QD 655 fluorescence (averaged surface density was 0.18 ± 0.006, five separate cultures), confirming that the red fluorescence signal was specific and only detected the BBS tag, consistent with our previous reports on KCNQ1 trafficking in HEK293 cells and cardiomyocytes (Aromolaran et al, 2014; Kanner et al, 2018).…”
Section: Resultssupporting
confidence: 90%
“…It is well established that many hERG mutants with trafficking deficits can be rescued by incubating cells at low temperature; this treatment presumably supports a correct folding of the protein, which is otherwise compromised by the mutation [13,[25][26][27]. To examine whether the L69P mutation can be rescued in this manner we repeated the same experiments as in Figure 3(Ab) with cells incubated at 27°C.…”
Section: Functional Expression Of Herg-wt and Herg Mutantsmentioning
confidence: 99%
“…For surface labeling experiments, the BBS-hERG-YFP construct was utilized as previously described [13,14], with the 13-residue bungarotoxin-binding site (BBS) introduced in the extracellular S3-S4 loop of hERG. Cell surface and total ion-channel pools were assayed by flow cytometry in live, transfected HEK293 cells [13,15]. Briefly, 48 h post-transfection, cells cultured in 12-well plates gently washed with ice cold PBS containing Ca 2+ and Mg 2+ (in mM: 0.9 CaCl 2 , 0.49 MgCl 2 , pH 7.4), and then incubated for 30 min in blocking medium (DMEM with 3% BSA) at 4ºC.…”
Section: Facs Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As Kv11.1a proteins traffic through the Golgi apparatus, the N-linked glycans on Kv11.1 α-subunit channel proteins are terminally glycosylated and their molecular mass increases to~155 kDa [34]. At the cell surface membrane, Kv11.1 channels are continually internalized and recycle back to the cell surface membrane every couple of minutes for several hours before they are targeted for degradation in lysosomes [35,36]. There are several excellent reviews that detail Kv11.1 channel trafficking, chaperones, and the biophysical function of Kv11.1 channels/I Kr [15,16,31,37] This review is focused on the newer strategies being developed to treat LQT2 and identify new LQT2 patients before they suffer a life-threatening event.…”
Section: Kcnh2 Kv111 and Ikrmentioning
confidence: 99%